Effects of a science center outreach lab on school students' achievement – Are student lab visits needed when they teach what students can learn at school?. (August 2015) - Itzek-Greulich, Heike; Flunger, Barbara; Vollmer, Christian; Nagengast, Benjamin; Rehm, Markus; Trautwein, Ulrich
Abstract: This study examined the effectiveness of labwork settings in science education with a pretest-posttest design. Sixty-eight ninth-grade classes ( N = 1773) were randomly assigned to three experimental conditions and a control condition. The first condition was taught the topic of the chemistry of starch in School only, the second condition was taught in the Science Center Outreach Lab (SCOL) only, the third condition was taught in a combined setting encompassing both a SCOL visit and classroom learning ( SCOL & school ), and the fourth was a control condition. A multilevel analysis investigated differences in achievement with experimental conditions as predictors on the class level and gender, language spoken at home, and pretest scores as predictors on the student level. The intervention was effective in all three experimental conditions with higher achievement than the control condition. Students in the combined setting ( SCOL & school ), our reference group in the multilevel analysis, learned more than the students in the control condition. However, since students' achievement in the SCOL only and School only conditions did not differ significantly from the SCOL & school condition, it seems that the learning goals of the SCOL can also be achieved at school (at least when labwork is provided). Highlights: Intervention study shows substantial effects on 9th graders science achievement. Science achievement is equally high in each of the three experimental conditions. Successful implementation of cluster randomized field trial in science education. Need to critically assess attempts in fostering STEM achievement is highlighted.